Evaluating environmental forcing on nutritional condition of Engraulis anchoita larvae in a productive area of the Southwestern Atlantic Ocean - Diaz, Marina Vera (2018)
The main goal of this study was to examine the nutritional condition of Engraulis anchoita larvae during the austral spring-summer seasons of 2010/2011 and 2012/2013 in highly productive waters in the southwestern Atlantic Ocean called El Rincón. RNA/DNA (RDs) index and derived index of Growth performance (Gpf) were used. Significant differences were observed in average RDs indices for 2010/2011 (5.27 ± 3.26) and 2012/2013 (0.81 ± 0.44). A difference in the years was also observed in Growth performance with higher values in 2010/2011 (2.45 ± 1.83) compared to 2012/2013 (−0.03 ± 0.25). Anchovy larvae captured in 2010/2011 were in good condition (Gpf > 1). During 2012/2013, extremely high larval densities were observed although Gpf values were very low indicating poor larval condition. Chlorophyll dynamics differed between sampled periods, with higher maximum values during spring 2012 as compared to 2010. Concerning chlorophyll concentrations showed a sharp decline in the values for the rest of the 2012/2013 season. We propose that the low larval growth and condition observed during 2012/2013 may have resulted from a decrease in chlorophyll concentrations together with very large larval densities which enhanced the competition for food within the larval population. Our results reinforce the idea that satellite ocean color products can be valuable tools for understanding variability in ecosystem dynamics and its effects on reproductive success in fish.